Designing virtual reality exposure scenarios to treat anxiety in people with epilepsy: Phase 2 of the AnxEpiVR clinical trial - Lewis-Fung, Samantha; Tchao, Danielle; Gray, Hannah Gabrielle; Nguyen, Emma; Pardini, Susanna; Harris, Laurence R.; Calabia, Dale; Appel, Lora (Frontiers in Virtual Reality, 2023)
Introduction: Anxiety in people with epilepsy (PwE) is characterized by distinct features related to having the condition and thus requires tailored treatment. Although virtual reality (VR) exposure therapy is widely-used to treat a number of anxiety disorders, its use has not yet been explored in people with epilepsy. The AnxEpiVR study is a three-phase pilot trial that represents the first effort to design and evaluate the feasibility of VR exposure therapy to treat epilepsy-specific interictal anxiety. This paper describes the results of the design phase (Phase 2) where we created a minimum viable product of VR exposure scenarios to be tested with PwE in Phase 3. Methods: Phase 2 employed participatory design methods and hybrid (online and in-person) focus groups involving people with lived experience (n = 5) to design the VR exposure therapy program. 360-degree video was chosen as the medium and scenes were filmed using the Ricoh Theta Z1 360-degree camera. Results: Our minimum viable product includes three exposure scenarios: (A) Social Scene—Dinner Party, (B) Public Setting—Subway, and (C) Public Setting—Shopping Mall. Each scenario contains seven 5-minute scenes of varying intensity, from which a subset may be chosen and ordered to create a customized hierarchy based on appropriateness to the individual’s specific fears. Our collaborators with lived experience who tested the product considered the exposure therapy program to 1) be safe for PwE, 2) have a high level of fidelity and 3) be appropriate for treating a broad range of fears related to epilepsy/seizures. Discussion: We were able to show that 360-degree videos are capable of achieving a realistic, immersive experience for the user without requiring extensive technical training for the designer. Strengths and limitations using 360-degree video for designing exposure scenarios for PwE are described, along with future directions for testing and refining the product.